Penggunaan Extreme Programming Untuk Menunjang Perubahan Kebutuhan Dalam Proses Pembangunan Sistem Informasi Produksi - Kela Tulvina; Nurfia Oktaviani Syamsiah; Weishky Steven Dharmawan (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2022)
Production Information System is something that is very important for a industrial company. Reliable production management is a major determinant of the company's profit. In the current era of digitalization, the use of production information systems is a necessity so that company goals are achieved with minimal costs and efforts and a shorter time span. On the other hand, the creation of an information system that is intended for a company whose business has been running requires a special method so that the system can be utilized immediately. Therefore, the involvement of system users from the beginning to the end of the creation stage is very necessary. The flexibility of changing requirements should also be well managed by system developers. Extreme Programing (XP) provides this solution, due to its flexibility so that it is able to deliver systems according to user needs, which often experience changes during the system development period. Production Information System on CV. Multi Karya Pontianak is a case study that was adopted in this research. By applying XP, the researcher resulted in the achievement of user acceptance test results reaching 97%.